2021
DOI: 10.1021/acs.jchemed.1c00126
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Study Strategies and Habits: A Study with Undergraduate Students in Spain and the U.K.

Abstract: The approach that students take in their studies at university is critical not only for their academic success but is equally important in life-long learning for their career and professional development. Cognitive science has demonstrated that retesting oneself on material when learning enhances and promotes greater retention of knowledge compared to rereading the material. Learning that is spaced out over multiple study sessions also allows for greater retention of knowledge in the longer-term compared to "c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Research on effective study strategies has a long history (Hattie, Biggs and Purdie, 1996;Fleming, 2002) and there is no universal study pattern that suits all students. However, there is limited research on how students actually study and prepare for class (Tomes, Wasylkiw and Mockler, 2011;Boevé et al, 2016;Fergus et al, 2021;Gurung et al, 2022;Blasiman, Dunlosky and Rawson et al, 2017), despite the crucial role of study habits in students' learning progress and academic success (Lorås et al, 2021).…”
Section: Related Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on effective study strategies has a long history (Hattie, Biggs and Purdie, 1996;Fleming, 2002) and there is no universal study pattern that suits all students. However, there is limited research on how students actually study and prepare for class (Tomes, Wasylkiw and Mockler, 2011;Boevé et al, 2016;Fergus et al, 2021;Gurung et al, 2022;Blasiman, Dunlosky and Rawson et al, 2017), despite the crucial role of study habits in students' learning progress and academic success (Lorås et al, 2021).…”
Section: Related Researchmentioning
confidence: 99%
“…In a survey study by Fergus et al (2021) the temporal element of students' preparation process was examined by comparing undergraduate students in Spain and the UK. The study revealed differences in their study strategies and habits, particularly regarding the actual time of study and opinions on the most effective time for studying.…”
Section: Related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Students spend time outside of class on their coursework, but it is the quality and focus of that study time, like the use of self-testing, that is typically positively associated with grade outcomes (Hartwig and Dunlosky, 2012;Fergus, 2022). Students may understand that higher quality studying leads to better grade outcomes, but they don't always know how to implement it (Tomes et al, 2011;Fergus et al, 2021;Carpenter et al, 2024). To help students better assess their own learning, we must take a more meaningful approach to how instructors assess their learning.…”
mentioning
confidence: 99%